Pengaruh Model Problem Based Learning Menggunakan LKPD Kontekstual terhadap Kemampuan Pemecahan Masalah Matematika Siswa SMP - Agustinsa, Ringki; Anjasari, Vesi; Yensy, Nurul Astuty (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2023)
Students need to have mathematical problem solving abilities to be able to solve complex mathematical problems. Mathematical problem solving abilities consist of understanding, planning, solving, and reviewing. These abilities can be trained through the application of appropriate learning models. One model that can be used is the problem based learning model. This study aims to determine the effect of the problem based learning model using contextual student worksheet on the mathematical problem solving ability of the junior high school students. This type of research is a quasi-experimental research with a research design of One Group Pretest-Posttest Design. The population in this study were all seventh grade students of SMP Negeri 12 Lebong in the 2021/2022 academic year. The sample in this study were class VIIA students, totaling 23 students as an experimental class taken by purposive sampling technique. The instrument used in this study was a problem-solving ability test sheet in the form of description questions. Data analysis using descriptive and inferential statistics. The results showed that there were differences in students' math solving abilities before and after learning. Based on the research results, it can be concluded that there is a significant influence on the Problem Based Learning model on mathematical problem solving in class VII students of SMP Negeri 12 Lebong.